The Association between Employment- and Housing-Related Financial Stressors and Marital Outcomes during the 2007–2009 Recession - Robert C Stewart; Jeffrey P Dew; Yoon G Lee (Journal of Financial Therapy, 2017)
This study examined the association between recession-related employment problems, recession-related housing problems, and marital quality. It used a national sample of married couples between the ages of 18 and 55. The analyses revealed that housing problems were negatively associated with wives’ reports of marital satisfaction and positively associated with wives’ and husbands’ reports of divorce proneness. Feelings of economic pressure fully mediated the association between housing problems and wives’ marital satisfaction and housing problems and husbands’ feelings of divorce proneness. Feelings of economic pressure only partially mediated the association between housing problems and wives’ reports of divorce proneness. Interestingly, recession-related employment problems were not associated with participants’ marital quality.
Keywords: 2007-2009 Recession; Housing-Related Financial Stressors; Employment-Related Financial Stressors